The life history of Soyedina producta (Claassen) (Plecoptera: Nemouridae) in an Oregon summer-dry stream, with notes on its larval generic character development - Stewart, Kenneth W. (Illiesia, 2010)
Voltinism and life history of the low, but sustained, population of Soyedina producta were determined from monthly collections of larvae, and adults from emergence traps, over a 15-year period. Monthly numbers from the 5 best years,2003-2007, and selected months from 1994 to 2002 were used for determination of larval growth. Emergence phenology was determined from numbers of adults taken from emergence traps over the period 1994 to 2008. Head capsule widths of 180 larvae were measured. The life cycle was univoltineand greatly adapted to the physical conditions of the summer-dry stream. Adult emergence peaked in March. The incubation time for eggs was not determined, but early-instar larvae were first recorded in July. There was little growth through September and then a steady growth from October until the early spring emergence. No larvae were found in benthos samples from Aprilthrough June. The larval generic diagnostic character of lateral pronotalnotch was present in the smallest 0.33mm head-capsule width larvae collected, and all larvae had a distinctive dark pigment pattern. First wingpad development occurred at 0.81-0.84mm head capsule width, and they grew to an inside forewingpad length of up to 1.41mm. Number of cercal segments increased during development from 16-18 to 24-28.
Keywords: entomologija; entomology; new species; vrbnice; Plecoptera; nove vrste; Nemouridae; Soyedina producta; life history; Oregon